Universal Design for Learning to Help All Children Read | Education Links - and Deaf Child Worldwide (2018)
All children, with or without a disability, can learn to read and should have equal access to quality instruction. No single category of disability should be prioritized above others. , Christopher Tester discusses the Universal Design for Learning: Promoting Literacy for All Learners with Disabilities, a toolkit released in September 2018 for international education stakeholders. This toolkit supports the Universal Design for Learning (UDL) educational framework, which guides the development of flexible learning environments that accommodate individuals with learning differences. , Lead author Anne Hayes, M.Ed. discusses the Universal Design for Learning to Help All Children Read: Promoting Literacy for Learners with Disabilities, a toolkit released in September 2018 for international education stakeholders. This toolkit supports the Universal Design for Learning (UDL) educational framework, which guides the development of flexible learning environments that accommodate individuals with learning differences. , Related Using Information Communications Technologies To Implement Universal Design For Learning Enhancing Skills Acquisition for Students with Disabilities Access the Resource